Some prime numbers of the form [(mxn)-(m-1)] and[(mxn)-(m+1)] - Shwan Omer Abdalrahman, Bewar Sulaiman Abdi Hajani (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
Define formula for some prime numbers, when m ,n positive integer, such that m is even number and n each positive integer such that <n≤m divided two formula: Define shwan formula(1) & shwan formula(2) shwan formula(1): p=(m x n)-(m-1) if m,n is even number <n ≤m shwan formula(2): p=(mxn)-(m+1) m is even & n odd number <n <m This form we use cannot be true for all prime numbers, cannot be made into a general form, the type of this form is the way that the peime numbers are not one after the other